Measuring Pattern Separation in Hippocampus by in Situ Hybridization. Issue 8 (18th August 2022) - Eom, Kisang; Lee, Hyoung‐Ro
Abstract: Distinguishing different contexts is thought to involve a form of pattern separation that minimizes overlap between neural ensembles representing similar experiences. Theoretical models suggest that the dentate gyrus (DG) segregates cortical input patterns before relaying its discriminated output patterns to the CA3 hippocampal field. This suggests that the evaluation of neural ensembles in DG and CA3 could be an important means to investigate the process of pattern separation. In the past, measurement of entorhinal cortex (EC), DG, and CA3 ensembles was largely dependent upon in vivo electrophysiological recording, which is technically difficult. This protocol provides a method to instead measure pattern separation by a molecular method that provides direct spatial resolution at the cellular level. © 2022 Wiley Periodicals LLC. Basic Protocol : Measuring pattern separation by molecular methods